Assessing the SWOT Analysis Based on Operational Status of Micro Businesses Along Novaliches Bayan, Quezon City: Basis for Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to assess the operation of micro-businesses in terms of profile,operational status, and SWOT analysis.The results of this study reveal that the profile of micro-businesses in Novaliches Bayan,Quezon City, is below 50,000 for Starting capital, 5,000 – 10,000 for monthly income, and15,000 - 20,000 for monthly expenses, which belong to food, beverage and the tobaccoindustry. Micro-business owners are hands-on in the operation and consider the accessibilityof the location and where a lot of people pass by. Micro businesses adopt the latesttechnology because it’s what the business uses for posting or promoting products andservices. Technology is a big help in selling products to gain more profit and increase sales.Micro businesses utilize the equipment for kitchen utensils, stoves, dining sets, cookingequipment, and grillers by regularly checking it for small repairs and defects. Owners selectemployees based on how hardworking and trustworthy they are, choosing employees who aregood at selling, marketing, communicating, and negotiations. Micro businesses assess theSWOT analysis in terms of strengths as their loyal customers, weaknesses as store/servicecapacity, and opportunities as creating more loyal customers. The threats are seasonaldemand; the rainy season and summer are different.This study recommended that micro businesses should monitor their financial projections andsave money to innovate products for more sustainable income. Owners should invest inmodern equipment continue to maintain a good relationship with customers, and use that as amarketing tool for promoting the business. Owners must try to put the presence of theirbusiness online. Micro businesses should also use delivery services to fill the lack ofstore/service capacity and must adapt to trend products during rainy, summer seasons orseasonal demands.
Keywords: Business